Age-dependent changes of neural functions under glucose metabolism disorders - Shadenko, Viktoria N. (Experimental Biology and Biotechnology, 2020)
There is a brief review of literature data about relationship of violations glucose homeostasis and cognitive brain functions. A relationship was found between impaired glucose metabolism during the formation of insulin resistance (type 2 diabetes mellitus) with the changes observed in development of a number of neurodegenerative diseases (Alzheimer’s disease). It is provides information on the role of insulin and insulin receptors in metabolic processes, development of hyperglycemia and insulin resistance during ageing. The contribution of free radical mechanisms in development of cognitive impairment caused by metabolic glucose changes is also discussed.